1971
DOI: 10.1139/v71-273
|View full text |Cite
|
Sign up to set email alerts
|

Radiolysis of Hydrogen Sulfide at Very High Dose Rates. The Effect of SF61

Abstract: Gaseous H2S has been irradiated with electron pulses from a Febetron 705 at a dose rate of ~2 × 1027 eV g−1 s−1. For single pulse experiments, the yield of hydrogen is G(H2) = 12.0 ± 0.5, independent of pressure from at least 350 to 1600 Torr. Addition of SF6 reduces the yield to G(H2) = 7.9 ± 0.3 which is fairly close to that observed for pure H2S at low dose rates. The reduction, ΔG(H2) = 4.1 ± 0.3, agrees very well with the ion pair yield based on a W value of 25.3 eV.In multi-pulse irradiations, for pure H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

1973
1973
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
7
1
Order By: Relevance
“…Rcently several studies of the radiolysis of hydrogen sulfide have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and we have proposed a mechanism based on our measurements at high dose rates (13). While this mechanism is in general agreement with the observed yields there are problems which need further investigation.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…Rcently several studies of the radiolysis of hydrogen sulfide have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and we have proposed a mechanism based on our measurements at high dose rates (13). While this mechanism is in general agreement with the observed yields there are problems which need further investigation.…”
Section: Introductionsupporting
confidence: 78%
“…The proposed mechanism does not predict any dose rate effect in the range 10' ' -10'' eV g-' s-', yet we observed an increase from G(H2) = 12.0 f 0.5 to G(H2) = 13.1 f 0.4 over this range (13,14). To study this further we have measured HZ yields in both pure H2S and H2S-SF, mixtures from 1 x loz6 eV g-' s-I to 2 x 10' ' eV g-' s-I at room temperature.…”
Section: Introductioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Field emission sources delivering -60 and -3 ns pulses (Febetron 705 and 706) were used in the pulse radiolysis experiments. The dose per pulse was determined using N 20 as a dosimeter [12], taking G(N z ) = 12.4. The reaction vessels used in the pulse radiolysis experiments were cylindrical vessels (5 em long and 3.7 em internal diameter).…”
Section: Expe Rimental Proceduresmentioning
confidence: 99%